Pression ulcer related to medical devices: Integrative review: Pression ulcer related to medical devices: Integrative review - Girondi, Juliana Balbinot Reis (2020)
Abstract: Objectives: To identify and analyze the degree of evidence of published studies on nursing care for the prevention, diagnosis and treatment of pression ulcer caused by medical devices. Method: Integrated revision on nursing data bases; Latin-American and Caribbean on Health Science, Cumulative Index to Nursing and Allied, Medical Literature Analysis and Retrieval System Online, Web of Science, the Cochrane and Scientific Electronic Library Online and Elsevier, during the period between 2014 and 2018. The article’s information and results were presented on boards and the corpus analysis was arranged in three categories based on each theme: Prevention of pressure- related injuries caused by medical devices focusing on risk factors; Nursing Resources for diagnostic evaluation caused by pression ulcer of medical devices; Nursing care for the treatment of pression ulcer caused by medical devices. Results: 1163 articles were found in total and 12 of them were selected, however only two were classified as “strong level of evidence, and five as “weak level of evidence”. Conclusion: It is necessary researches focusing on the prevention, diagnosis and treatment in the Nursing area, as well as continuing educational actions aimed at instructing nurses to minimize the occurrence of pression ulcer caused by medical devices.